Pengaruh Penggunaan Media Sosial Instagram Terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPS di MTs Miftahul Huda Bekasi - Dina Junianti; Supriyadi; Irvia Eriza (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of Instagram social media usage on students’ learning achievement at MTs Miftahul Huda Bekasi. The background of this research is based on the phenomenon of increasing social media use among teenagers, particularly Instagram, which is assumed to have both positive and negative impacts on students’ academic performance. The research method employed was quantitative associative. The research sample consisted of 77 students selected using the simple random sampling technique. The instruments used were a questionnaire on Instagram usage and documentation of report card grades as indicators of learning achievement. Data analysis was carried out using simple correlation tests, the coefficient of determination, and simple regression analysis. The results showed that the use of Instagram social media did not have a significant effect on students’ learning achievement at MTs Miftahul Huda Bekasi. This was evidenced by the regression equation: X = 75.748 + 0.12 Y. From the analysis, the t-test value was 1.254 with a significance level of 0.214. Therefore, H₀ was accepted and H₁ was rejected. This indicates that the Instagram usage variable does not significantly influence students’ academic achievement. Meanwhile, the coefficient of determination (R²) was 0.021, which means that only 2.1% of the variation in learning achievement was explained by this variable, while the remaining percentage was influenced by other factors.